Murine Models for the Study of Fetal Alcohol Spectrum Disorders: An Overview - Almeida, Laura; Andreu-Fernández, Vicente; Navarro-Tapia, Elisabet; Aras-López, Rosa; Serra-Delgado, Mariona; Martínez, Leopoldo; García-Algar, Oscar; Gómez-Roig, María Dolores (Frontiers in Pediatrics, 2020)
Prenatal alcohol exposure is associated to different physical, behavioral, cognitive, and neurological impairments collectively known as Fetal Alcohol Spectrum Disorders. The underlying mechanisms of ethanol toxicity are not completely understood. Experimental studies during human pregnancy to identify new diagnostic biomarkers are difficult to carry out beyond genetic or epigenetic analyses in biological matrices. Therefore, animal models are a useful tool to study the teratogenic effects of alcohol on the central nervous system and analyze the benefits of promising therapies. Animal models of alcohol spectrum disorder allow the analysis of key variables such as amount, timing and frequency of ethanol consumption to describe the harmful effects of prenatal alcohol exposure. In this review, we aim to synthetize neurodevelopmental disabilities in rodent fetal alcohol spectrum disorder phenotypes, considering facial dysmorphology and fetal growth restriction. We examine the different neurodevelopmental stages based on the most consistently implicated epigenetic mechanisms, cell types and molecular pathways, and assess the advantages and disadvantages of murine models in the study of fetal alcohol spectrum disorder, the different routes of alcohol administration, and alcohol consumption patterns applied to rodents. Finally, we analyze a wide range of phenotypic features to identify fetal alcohol spectrum disorder phenotypes in murine models, exploring facial dysmorphology, neurodevelopmental deficits, and growth restriction, as well as the methodologies used to evaluate behavioral and anatomical alterations produced by prenatal alcohol exposure in rodents.